ANALYSIS OF THE PERCEPTIONS OF ACADEMICS AND PRACTITIONERS IN MEDAN REGARDING THE CONTRIBUTION OF GREEN SUKUK IN SUPPORTING SUSTAINABLE DEVELOPMENT GOALS (SDGS) IN INDONESIA - Rahmi, Siti; Sugianto; Jannah, Nurul (Journal of Sharia Economics, 2026)
This study aims to analyze the perceptions of academics and practitioners in Medan regarding the contribution of Green Sukuk in supporting SDGs in Indonesia. This study uses a descriptive qualitative approach with in-depth interviews with eight key informants consisting of four academics and four capital market practitioners. The results show a consensus that Green Sukuk has made a tangible physical contribution through strategic projects, particularly in North Sumatra, such as the Kuala Namu Airport railway line and solar energy development. However, there is a difference in orientation between academics, who view SDGs as a systemic obligation in line with the principles of Maqashid Shariah, and practitioners, who tend to view them from the perspective of regulatory compliance and corporate reputation management. The main challenges identified include low investor literacy, issues of investor economic rationality, and the absence of quantitative environmental impact measurement standards. This study recommends the need for policy synchronization between institutions and the provision of fiscal incentives to expand the green finance market in Indonesia.